Transferência de política pública e o papel do embaixador de políticas: dos Parques-Biblioteca de Medellín para os Centros Comunitários da Paz no Recife - Ana Pollinny de Freitas; Eliane Superti; Liliana Ramalho Fróio (Colombia Internacional)
Objective/context: This article analyzes how public policy (PP) crosses national borders and diffuses into another political space, focusing on the role of paradiplomatic actors in the Northeast Region of Brazil. Specifically, it examines the transfer of the experience of Medellín’s Library Parks in Colombia to the creation of the Peace Community Centers in Recife, Brazil. The main objective was to analyze the transfer process and the role played by the public policy ambassador. Methodology: The methodology used includes literature review, semi-structured interviews, field visits, and document analysis. Conclusions: It is identified that the translation of the policy was emulation; that is, Recife’s PP bears similarity to Medellín’s, with adaptations and adjustments to its reality. The mechanisms through which the process occurred were mainly three: networking, circulation of individuals, and social construction. The research pointed out that the PP ambassador, represented by the former Secretary of Citizen Security of Recife, played a crucial role in the internationalization, adaptation, and implementation of this policy. Originality: The article contributes to the debate on the diffusion of public policies, especially in the context of peripheral subnational regions, and highlights the importance of the role of PP ambassadors in mediating and adapting international experiences to local contexts.